2010
DOI: 10.1093/brain/awq276
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogens ameliorate mitochondrial dysfunction in Leber’s hereditary optic neuropathy

Abstract: Leber's hereditary optic neuropathy, the most frequent mitochondrial disease due to mitochondrial DNA point mutations in complex I, is characterized by the selective degeneration of retinal ganglion cells, leading to optic atrophy and loss of central vision prevalently in young males. The current study investigated the reasons for the higher prevalence of Leber's hereditary optic neuropathy in males, exploring the potential compensatory effects of oestrogens on mutant cell metabolism. Control and Leber's hered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
152
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(171 citation statements)
references
References 45 publications
(75 reference statements)
12
152
1
6
Order By: Relevance
“…Thus far, these explanations are simply theories that require further investigation. Why the male sex appears to be a risk factor for ischemic optic neuropathy during prone position is still a puzzle, but it has been suggested that estrogen may serve a protective role [31] .…”
Section: Theoretical Mechanisms For Ischemic Optic Neuropathy After Pmentioning
confidence: 99%
“…Thus far, these explanations are simply theories that require further investigation. Why the male sex appears to be a risk factor for ischemic optic neuropathy during prone position is still a puzzle, but it has been suggested that estrogen may serve a protective role [31] .…”
Section: Theoretical Mechanisms For Ischemic Optic Neuropathy After Pmentioning
confidence: 99%
“…Recently Giordano et al . [71] investigated the effects of oestrogens on cybrids carrying the LHON mutations 11778/ND4, 3460/ND1 and 14484/ND6 in vitro . Treatment with 17β-oestradiol reduced levels of reactive oxygen species (ROS), believed to be responsible for oxidative cell damage which had previously been shown to be raised in LHON cells.…”
Section: Leber Hereditary Optic Neuropathy (Lhon Mitochondrial)mentioning
confidence: 99%
“…For example, the G11778A (ND4) and T14484C (ND6) LHON mutations on subgroups of a mitochondrial haplogroup J or the G3460A (ND1) mutation on the mitochondrial haplotype K background have been associated with increased risk of visual loss [29]. Differences between haplogroups may be partially due to mtDNA quantity, which influences OXPHOS capacity [30] and may account for gender differences in disease penetrance in LHON; there is a suggestion that oestrogens increase mtDNA levels, enhancing oxygen consumption and ATP generation [87]. associated with specific mitochondrial mutations.…”
Section: Cellular Models Of Mitochondrial Diseasementioning
confidence: 99%